Implementing and measuring person-centredness using an APP for knowledge transfer: the iMPAKT app. (25th March 2020) - McCance, Tanya; Lynch, Brighide M; Boomer, Christine; Brown, Donna; Nugent, Christopher; Ennis, Andrew; Garcia-Constantino, Matias; Clelland, Ian; Edgar, Denise; Radbron, Emma; Wilson, Valerie
Abstract: Objective: The aim of the study was to evaluate a technological solution in the form of an App to implement and measure person-centredness in nursing. The focus was to enhance the knowledge transfer of a set of person-centred key performance indicators and the corresponding measurement framework used to inform improvements in the experience of care. Design: The study used an evaluation approach derived from the work of the Medical Research Council to assess the feasibility of the App and establish the degree to which the App was meeting the aims set out in the development phase. Evaluation data were collected using focus groups ( n = 7) and semi-structured interviews ( n = 7) to capture the impact of processes experienced by participating sites. Setting: The study was conducted in the UK and Australia in two organizations, across 11 participating sites. Participants: 22 nurses from 11 sites in two large health care organizations were recruited on a voluntary basis. Intervention: Implementing the KPIs and measurement framework via the APP through two cycles of data collection. Main Outcome Measures: The main outcome was to establish feasibility in the use of the App. Results: The majority of nurse/midwife participants found the App easy to use. There was broad consensus that the App was an effective method to measure the patient experience and generated clear, concise reports in real time. Conclusions: The implementation of the person-centred key performance indicators using the App enhanced the generation of meaningful data to evidence patient experience across a range of different clinical settings.